Technologies in the mapping of slipping risk areas in Teófilo Otoni (Research, Society and Development, 2019)
The growth of the urban population is currently a concern of the public power and population, since it generates an occupation at a fast pace, constantly carried out without planning. To do so, it is necessary to identify areas susceptible to geological risk, in order to protect the population from the occurrence of landslides, in addition to recovering and protecting spaces already occupied. The present study aims to develop an evaluation method with the aid of Geoprocessing software in Geographic Information Systems (GIS), which provides the mapping of areas susceptible to mass gravitational movements located in the urban areas of Teófilo Otoni. In order to do so, the study area was delimited, followed by the identification and qualification of danger areas to planar landslide gravitational movements and, finally, risk qualification in some of these areas. This time, thirty-five areas of danger to planar landslide processes were identified and qualified, and the risk areas present in three of the districts of the municipality were delineated and classified, demonstrating that the use of geoprocessing technologies in a GIS platform satisfactorily provided the mapping of risk areas in urban spaces.